THE INFLUENCE OF PRODUCT QUALITY, SERVICE QUALITY, AND TIMELINESS OF DELIVERY ON REPURCHASE INTENTION AT CAKE BY TENGGILIS SURABAYA - Felisa Amelia Candra; J.E. Sutanto; Michael Ricky Sondak (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The study entitled “The Influence of Product Quality, Service Quality, and Timeliness of Delivery on Repurchase Intention at Cake by Tenggilis Surabaya” has four objectives, namely: (1) Knowing the effect of product quality on repurchase intention, (2) Knowing the effect of service quality on repurchase intention, (3) Knowing the effect of timeliness of delivery on repurchase intention, (4) Knowing the effect of product quality, service quality, and timeliness of delivery on repurchase intention simultaneously. Cake by Tenggilis Surabaya is a business engaged in the food industry, specifically a cake shop. This research uses quantitative methods. The population in this study was the customers of Cake by Tenggilis. The sample in this study amounted to 150 respondents. Data were collected through questionnaires which were distributed online using google forms. In this study, the data were processed using SPSS 22 for windows. The results of this study are: (1) Product quality has a significant effect on repurchase intention, (2) Service quality has a significant effect on repurchase intention, (3) Timeliness of delivery has a significant effect on repurchase intention, also (4) Product quality, service quality, and timeliness of delivery simultaneously have a significant effect on repurchase intention.